Cervical cancer testing among women aged 30–49 years in the WHO European Region. (7th September 2021) - Williams, Julianne; Rakovac, Ivo; Victoria, Jocelyn; Tatarinova, Tatiana; Corbex, Marilys; Barr, Ben; Rose, Tanith; Sturua, Lela; Obreja, Galina; Andreasyan, Diana; Shukurov, Shukhrat; Gahraman, Hagverdiyev; et al.
Abstract: Background: Screening programs play an important role in a comprehensive strategy to prevent cervical cancer, a leading cause of death among women of reproductive age. Unfortunately, there is a dearth of information about rates of cervical cancer testing, particularly in Eastern Europe and Central Asia where levels of cervical cancer are among the highest in the WHO European Region. The purpose of this article is to report on the lifetime prevalence of cervical cancer testing among females aged 30–49 years from across the WHO European region, and to describe high-level geographic and socioeconomic differences. Methods: We used data from the European Health Information Survey and the WHO STEPwise approach to Surveillance survey to calculate the proportions of women who were tested for cervical cancer. Results: The percentage of tested women ranged from 11.7% in Azerbaijan to 98.4% in Finland, with the lowest percentages observed in Azerbaijan, Tajikistan and Uzbekistan. Testing was lower in Eastern Europe (compared to Western Europe), among low-income countries and among women with lower levels of education. Conclusion: Effective cervical cancer screening programs are one part of a larger strategy, which must also include national scale-up of human papilloma virus vaccination, screening and treatment.